(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article discusses the issues of popularization and reading of economic literature and its educational impact. As part of the study, the author draws attention to the need to study and promote the works of authors who have left an indelible mark on the history of mankind. The article describes the purpose of reading and popularizing economic literature and its influence on people’s consciousness. The study draws attention to the role of economic literature in the educational process. The author provides conclusions and recommendations in the area under studyKeywords: economic literature, Adam Smith, David Ricardo, Thomas Robert Malthus, Ibn Khaldun, François Quesnay, Antoine de Montchretien, Karl Marx, Leon Walras, Carl Menger, Alfred Marshall